FILLER PIPE - OZAKI TOMOAKI (2015)
PROBLEM TO BE SOLVED: To provide a filler pipe that has a simple structure, and can prevent an oil supply gun from malfunctioning and droplets from being blown back.SOLUTION: A screw part is formed in an entrance part of a filler pipe, and a plurality of projection parts which projects inward are formed inwardly beyond the screw part of the filler pipe. A retainer 20 has a retainer tip part 21, a retainer fitting part 22, and a retainer opening part 23. A spiral retainer screw part 24 is formed over from a root of the retainer tip part 21 to the retainer fitting part 22, the retainer tip part 21 has a plurality of retainer tip cut parts 21a formed in an axial direction, and the projection parts of the filler pipe are fitted in the retainer tip cut parts 21a. 【課題】構造も簡単で、給油ガンの誤作動や液滴の吹き返しを防止できる、フィラーパイプを提供する。【解決手段】フィラーパイプの入口部の内部に、ねじ部を形成するとともに、フィラーパイプのねじ部よりも奥に、複数の内側に突出する凸部を形成する。リテーナ２０は、リテーナ先端部２１とリテーナ取付部２２とリテーナ開口部２３を有する。リテーナ先端部２１の根元からリテーナ取付部２２に亘りらせん状のリテーナねじ部２４を形成し、リテーナ先端部２１には、軸方向に複数のリテーナ先端切欠き部２１ａを形成し、リテーナ先端切欠き部２１ａにフィラーパイプの凸部を嵌合した。【選択図】図１